A peptidomic approach of meat protein degradation in a low-sodium fermented sausage model using autochthonous starter cultures - de Almeida M.A. (2018)
We wish to thank Centro de Referencia para Lactobacilos (CERELA-CONICET) collection for supplying the strains. We would also like to thank IBRAC and Sealed Air-Brazil that provided the additives and packaging, respectively. M. Almeida received the support of the Coordenacao de Aperfeicoamento de Pessoal de Nivel Superior (CAPES), PhD scholarship from Brazil and E. Saldaña received the support of the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica - CONCYTEC” from Perú (CIENCIACTIVA programme, PhD scholarship contract agreement No. 104-2016-FONDECYT). This study was financially supported by the São Paulo Research Foundation (FAPESP) Project No.2012/07113-2; project AGL2012-32146 from MINECO (Spain) and PIP2011-0100406 and PIP2015-0530 from CONICET.